Dental Treatment for Overgrown Teeth in a Black-Spotted Pufferfish (Arothron nigropunctatus) - Fecchio, Roberto Silveira; Dutra, Gustavo P.; Barbosa, Bruna Emely Pereira; Lucena, Marcel de Freitas; Teixeira, Rodrigo Hidalgo Friciello [UNESP] (SAGE Publications, 2025)
Pufferfish, known for their unique dental structures and body features, can face complications such as overgrown teeth, leading to difficulties in feeding and potential health issues. This study aims to report the diagnosis, treatment plan, and outcomes of a dental intervention addressing a case of overgrown teeth in a black-spotted pufferfish (Arothron nigropunctatus) housed in an aquarium in the southeastern region of Brazil. The article discusses the challenges encountered during the treatment process and provides insights into the importance of proactive dental care in aquatic species. The successful resolution of the case highlights the significance of tailored dental interventions in ensuring the well-being of aquatic species, like the pufferfish. Furthermore, this study documents the first dental treatment performed on a pufferfish specimen in Brazil.
Keywords: aquarium; dentistry; fish medicine; Tetraodontiformis; tooth